TECHNOLOGICAL METHODS OF PROCESSING FRUITS AND VEGETABLES (Scientific journal of the Fergana State University, 2026)
The methods of fruit processing are aimed at halting biological and physiological processes within them, completely eliminating phytopathogenic microbes, and isolating the products from the external environment. Fruits are mainly processed using physical, microbiological, and chemical methods. Modern technologies are focused on minimizing the loss of vitamins and other beneficial biological compounds in the products.